Transactional Links Between Social Anxiety Symptoms and Parenting Across Adolescence: Between‐ and Within‐Person Associations. Issue 3 (30th March 2019) - Nelemans, Stefanie A.; Keijsers, Loes; Colpin, Hilde; van Leeuwen, Karla; Bijttebier, Patricia; Verschueren, Karine; Goossens, Luc
Abstract : This 4‐year longitudinal multi‐informant study examined between‐ and within‐person associations between adolescent social anxiety symptoms and parenting (parental psychological control and autonomy support). A community sample of 819 adolescents (46.1% girls; M age T1  = 13.4 years) reported annually on social anxiety symptoms and both adolescents and mothers reported on parenting. Between‐person associations suggested that adolescent social anxiety symptoms were associated with higher adolescent‐ and mother‐reported psychological control and lower mother‐reported autonomy support. At the within‐person level, however, mothers reported lower psychological control and higher autonomy support after periods with higher adolescent social anxiety symptoms. Our findings illustrate the importance of distinguishing among between‐person and within‐person associations and including perceptions of both dyad members in longitudinal research concerning parenting and adolescent mental health.